Strategic Adaptation in the Post-Pandemic Business Landscape: Challenges and Opportunities - Suryo Mulyono, Nugroho; Saida Zainurossalamia ZA (International journal of technology and education research, 2025)
The COVID-19 pandemic has dramatically changed the global business landscape, forcing companies to adapt quickly to new challenges and emerging opportunities. This article aims to explore the adaptation strategies adopted by different sectors in the face of these changes. By analyzing recent literature and case studies, we identify key factors that influence the success of strategic adaptation, including technological innovation, changing consumer behavior, and risk management. In addition, this article discusses the challenges companies face, such as economic uncertainty and supply chain issues. We also highlight emerging opportunities, including digitalization and sustainability, which can be growth drivers in the post-pandemic era. The results of this study provide valuable insights for stakeholders in formulating effective strategies to survive and thrive amidst changing market dynamics.